2016
DOI: 10.1007/s11270-016-2768-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of Wastewater and Biosolids in Soil: Occurrence and Fate of Emerging Contaminants

Abstract: Wastewater (WW) for irrigation and application of biosolids in soil is becoming important as it is going to become very common in the near future. By 2050, the world is going to have four billion people living in water-scarce countries, making it a norm of freshwater for the cities and WW for agriculture. Further, biosolids might still be used as green biofertilizers for soils, if they are improved from an ecological point of view. However, application of biosolids in soil is argued because of the amount of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 95 publications
0
38
0
Order By: Relevance
“…In this perspective, sludge can be also transformed, e.g., into biofertilisers. This application may change the soil microbial community composition (Mohapatra et al 2016). However, field application of sludge-based organic fertilisers could be virtually neglected because of additional load of microorganism introduced into the soil with that kind of fertilisers.…”
Section: Introductionmentioning
confidence: 99%
“…In this perspective, sludge can be also transformed, e.g., into biofertilisers. This application may change the soil microbial community composition (Mohapatra et al 2016). However, field application of sludge-based organic fertilisers could be virtually neglected because of additional load of microorganism introduced into the soil with that kind of fertilisers.…”
Section: Introductionmentioning
confidence: 99%
“…The findings are of high relevance to the emergence of antibiotic resistance in some natural and built environments. High pesticide levels (mg/L) triggering evolution towards resistance may occur in biosolids and aquatic organisms where pesticides can be accumulated (49-51). In aquatic environments receiving WWTP effluent and agricultural runoff, antibiotics at sub-MIC levels are occurring together with pesticides at ng - µg/L (20-24).…”
Section: Discussionmentioning
confidence: 99%
“…The use of both treated and untreated reclaimed wastewater and biosolids in agriculture is a widely adopted practice in countries suffering from water shortages such as Mexico, Israel, Australia and Southern Europe. (Asano et al 2007;Pedrero et al 2010;Dalkmann et al 2012;Lees et al 2016) Further, crops are grown on agricultural soils and cattle producing meat and milk are grazing on grasslands that have been amended with sludge-based biosolids and/or reclaimed wastewater, which poses a potential risk of indirect human exposure via these products (Mohapatra et al 2016;Paz et al 2016;Kinney et al 2006a), which was previously demonstrated (Mottaleb et al 2016;Franklin et al 2016;Malchi et al 2014).…”
Section: Why a New Prioritization Framework Is Neededmentioning
confidence: 99%
“…Extensive patient and veterinary use, incomplete metabolism, continuous use by society, and lack of rapid biodegradability of many active pharmaceutical ingredients (APIs) resulted in their ubiquitous presence in various environmental media (Redshaw et al 2013;Gaw and Brooks 2016;Bergheim et al 2014), and detection in non-target organisms (Miller et al 2015;Tanoue et al 2015;Cuthbert et al 2014). Pharmaceuticals can reach the environment via multiple point source and diffuse pathways including incomplete removal in conventional wastewater treatment and subsequent release into surface waters (Luo et al 2014); release of untreated wastewater directly or through combined sewer overflows (CSOs) (Mennigen et al 2011;Phillips et al 2012); migration in landfill leachate (Masoner et al 2016); agricultural use and sludge spreading (Mohapatra et al 2016); domestic septic tank discharge (Yang et al 2016); and release of manufacturing effluent (Cardoso et al 2014;Larsson 2014).…”
Section: Introductionmentioning
confidence: 99%